Polyol composition and urethane resin composition

The polyol composition with a specific foaming agent content and the inclusion of carbon dioxide in the urethane resin composition address the issue of increased density and poor stability in polyurethane foams at low temperatures, achieving improved dimensional stability and reduced material needs.

JP7653290B2Active Publication Date: 2025-03-28SEKISUI CHEMICAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021062081
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-03-28
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Conventional polyurethane foam formation methods using spray foaming result in increased density at low temperatures, leading to higher raw material requirements for achieving the desired thickness and poor dimensional stability.

Method used

A polyol composition containing polyol, filler, foaming agent, resinization catalyst, and trimerization catalyst, with a specific range of foaming agent content (35 to 60 parts by mass per 100 parts by mass of polyol), is used to form a urethane resin composition that includes critical, subcritical, or liquid carbon dioxide, enhancing foaming properties and suppressing high density.

Benefits of technology

The solution effectively suppresses high density in polyurethane foams at low temperatures and improves dimensional stability, ensuring the polyurethane foam maintains the desired properties and reduces material requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653290000001
    Figure 0007653290000001
  • Figure 0007653290000002
    Figure 0007653290000002
  • Figure 0007653290000003
    Figure 0007653290000003
Patent Text Reader

Abstract

To provide a polyol composition that can form polyurethane foam less prone to increased density at low temperatures and having high dimensional stability.SOLUTION: A polyol composition contains a polyol, a filler, a foamer, a resinification catalyst and a trimerization catalyst, where the content of the foamer is 35-60 pts.mass relative to the polyol 100 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyol composition and a urethane resin composition for forming a polyurethane foam. [Background technology]

[0002] Conventionally, polyurethane foams have been used as heat insulating materials in vehicles such as automobiles, building materials, etc. In general, polyurethane foams are formed by discharging and mixing a polyol composition and a polyisocyanate composition filled in separate containers.

[0003] Polyurethane foams are generally formed by foaming with a foaming agent contained in a polyol composition. Water, hydrofluoroolefins, etc. are generally used as the foaming agent. However, from the viewpoint of improving the physical properties of polyurethane foam, various blowing agents are being investigated. For example, Patent Documents 1 to 4 disclose a method for producing polyurethane foam at a polyurethane foam production site by adding a certain amount of carbon dioxide (supercritical, subcritical or liquid carbon dioxide) as a blowing agent to at least one of a polyol composition and a polyisocyanate composition. It is described that this method can produce polyurethane foam with flame retardancy and uniform density distribution. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-070409 A [Patent Document 2] JP 2020-070410 A [Patent Document 3] JP 2020-070411 A [Patent Document 4] JP 2020-128458 A Summary of the Invention [Problem to be solved by the invention]

[0005] The above-mentioned conventional methods mainly use a spray foaming method in which a polyol composition and a polyisocyanate composition are sprayed onto an adherend using a spray gun or the like, and then foamed and cured to form a polyurethane foam. The polyurethane foam formed by the spray foaming method is used in an environment that is almost the same as the outside temperature, and its density changes depending on the outside temperature. For example, when the temperature is low, cell growth is inhibited, and the density of the polyurethane foam increases, and at extremely low temperatures, the curing speed slows down, and the blowing agent easily escapes as a gas, which tends to increase the density even more. Thus, in a low temperature environment (e.g., -5 to 10°C), a polyurethane foam having a higher density than intended is formed, and there is also the problem that more raw materials are required to form a polyurethane foam of a specified thickness.

[0006] Therefore, an object of the present invention is to provide a polyol composition capable of forming a polyurethane foam that can suppress densification in a low-temperature environment and has excellent dimensional stability, and a urethane resin composition containing the polyol composition. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive research and found that the above-mentioned problems can be solved by a polyol composition comprising a polyol, a filler, a foaming agent, a resinification catalyst, and a trimerization catalyst, in which the content of the foaming agent is within a specific range, and a urethane resin composition comprising the polyol composition, thereby completing the present invention. That is, the present invention relates to the following [1] to

[11] .

[0008] [1] A polyol composition comprising a polyol, a filler, a foaming agent, a resinification catalyst and a trimerization catalyst, the content of the foaming agent being 35 to 60 parts by mass per 100 parts by mass of the polyol. [2] The polyol composition according to the above [1], wherein the blowing agent is at least one selected from the group consisting of water and hydrofluoroolefins. [3] A urethane resin composition comprising the polyol composition according to [1] or [2] above and a polyisocyanate composition containing a polyisocyanate. [4] The core density of the resulting polyurethane foam is 25-45 kg / m 3 The urethane resin composition according to the above [3], [5] The urethane resin composition according to [3] or [4] above, which contains supercritical, subcritical or liquid carbon dioxide. [6] The urethane resin composition according to any one of the above [3] to [5], wherein the resinification catalyst comprises at least one metal-based resinification catalyst selected from the group consisting of bismuth-based catalysts and tin-based catalysts. [7] The urethane resin composition according to the above [6], wherein the content of the metal resinification catalyst is 0.1 to 12 parts by mass per 100 parts by mass of the polyol. [8] The urethane resin composition according to any one of the above [3] to [7], wherein the trimerization catalyst contains a quaternary ammonium salt. [9] The urethane resin composition according to any one of the above [3] to [8], wherein the trimerization catalyst contains a quaternary ammonium salt and an alkali metal carboxylate, and the weight ratio thereof (quaternary ammonium salt / alkali metal carboxylate) is 1 / 1 to 6 / 1.

[10] The urethane resin composition according to any one of the above [3] to [9], wherein the content of the trimerization catalyst is 1 to 30 parts by mass per 100 parts by mass of the polyol.

[11] A method for producing a polyurethane foam by foaming and curing the urethane resin composition according to any one of the above [3] to

[10] , A method for producing a polyurethane foam, comprising the step of adding critical, subcritical or liquid carbon dioxide to at least one of a polyol composition and a polyisocyanate composition, the amount of carbon dioxide added being 0.1 to 4 parts by mass per 100 parts by mass of the polyol, and a reaction proceeding after the addition of the carbon dioxide. Effect of the Invention

[0009] According to the present invention, it is possible to provide a polyol composition capable of forming a polyurethane foam which is capable of suppressing densification in a low-temperature environment and has excellent dimensional stability, and a urethane resin composition containing the polyol composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The polyol composition of the present invention contains a polyol, a filler, a foaming agent, a resinification catalyst, and a trimerization catalyst, and the content of the foaming agent is 35 to 60 parts by mass based on 100 parts by mass of the polyol. The present invention will be described in detail below.

[0011] [Polyol composition] The polyol composition of the present invention comprises a polyol, a filler, a blowing agent, a resinification catalyst and a trimerization catalyst.

[0012] <Foaming agent> The polyol composition contains a foaming agent. The content of the foaming agent is 35 to 60 parts by mass relative to 100 parts by mass of the polyol. If the content of the foaming agent is less than 35 parts by mass, the foaming property is reduced, and a polyurethane foam with high density is formed in a low-temperature environment. On the other hand, if the content of the foaming agent is more than 60 parts by mass, the dimensional stability of the polyurethane foam formed is reduced, and problems such as falling off from the adherend are likely to occur. From this viewpoint, the content of the blowing agent relative to 100 parts by mass of the polyol is preferably 38 to 55 parts by mass, and more preferably 40 to 50 parts by mass.

[0013] The blowing agent is not particularly limited, but preferably includes, for example, water, a hydrocarbon compound, a chlorinated aliphatic hydrocarbon compound, a hydrofluorocarbon, a hydrochlorofluorocarbon compound, a hydrofluoroolefin, etc. Among them, from the viewpoints of good foam formation and reducing the environmental load, the blowing agent is preferably at least one selected from the group consisting of water and hydrofluoroolefin. By containing the hydrofluoroolefin, when a filler described below is used, the dispersibility of the filler in the foam is improved. From the viewpoint of improving foaming properties, the foaming agent preferably contains water, and more preferably contains both water and a hydrofluoroolefin.

[0014] Examples of the hydrofluoroolefin contained in the blowing agent include fluoroalkenes having 3 to 6 carbon atoms. The hydrofluoroolefin may be a hydrochlorofluoroolefin having a chlorine atom, and therefore may be a chlorofluoroalkene having 3 to 6 carbon atoms. The hydrofluoroolefin preferably has 3 or 4 carbon atoms.

[0015] The hydrofluoroolefin used as the blowing agent preferably has a boiling point of more than 0°C at 1 atmospheric pressure, and examples thereof include (E)-1-chloro-3,3,3-trifluoropropene (HFO-1233zd(E)), (Z)-1-chloro-3,3,3-trifluoropropene (HFO-1233zd(Z)), (Z)-1,1,1,4,4,4-hexafluorobut-2-ene (HFO-1336mzz(Z)), (E)-1,1,1,4,4,4-hexafluorobut-2-ene (HFO-1336mzz(E)), (Z)-1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd(Z)), and the like.

[0016] The content of the hydrofluoroolefin used as a blowing agent is preferably 35 to 55 parts by mass, more preferably 38 to 53 parts by mass, and even more preferably 40 to 50 parts by mass, per 100 parts by mass of polyol, from the viewpoints of suppressing densification of the polyurethane foam in a low-temperature environment and improving the dimensional stability.

[0017] The content of water used as a blowing agent is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and even more preferably 0.5 to 3 parts by mass, per 100 parts by mass of polyol, from the viewpoint of setting the density of the polyurethane foam in the desired range.

[0018] <Catalyst> The polyol composition contains a resinification catalyst and a trimerization catalyst. The resinification catalyst is a catalyst that promotes the reaction between a polyol and a polyisocyanate, and the trimerization catalyst is a catalyst that promotes the reaction of an isocyanate group contained in the polyisocyanate to trimerize it, thereby promoting the formation of an isocyanurate ring.

[0019] (Resinification catalyst) Examples of the resinification catalyst include metal-based resinification catalysts, amine-based resinification catalysts, etc. Among them, from the viewpoint of suppressing the increase in density of the polyurethane foam formed in a low-temperature environment, the resinification catalyst preferably contains at least one metal-based resinification catalyst selected from the group consisting of bismuth-based catalysts and tin-based catalysts, and more preferably contains a metal-based resinification catalyst consisting of a bismuth-based catalyst.

[0020] The bismuth catalyst is preferably a bismuth salt of a carboxylic acid having 5 or more carbon atoms. More specifically, the bismuth catalyst is preferably a bismuth carboxylate such as bismuth octoate, such as bismuth 2-ethylhexanoate, bismuth neodecanoate, or bismuth naphthenate, and among these, bismuth 2-ethylhexanoate is more preferable. The tin-based catalyst is preferably a tin salt of a carboxylic acid having 5 or more carbon atoms. More specifically, the tin-based catalyst is preferably a tin salt of a carboxylic acid such as tin acetate, tin 2-ethylhexanoate, tin oleate, tin laurate, dibutyltin diacetate, dimethyltin dilaurate, dibutyltin dilaurate, dibutyltin dineodecanoate, dioctyltin dineodecanoate, or dioctyltin dilaurate, and among these, dioctyltin dineodecanoate is more preferable.

[0021] The content of the metal resinification catalyst is preferably 0.1 to 12 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 2 to 8 parts by mass, based on 100 parts by mass of the polyol.

[0022] Examples of the amine resinification catalyst include imidazole compounds, pentamethyldiethylenetriamine, triethylamine, N-methylmorpholinebis(2-dimethylaminoethyl)ether, bis(2-dimethylaminoethyl)ether, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N'-trimethylaminoethyl-ethanolamine, bis(2-dimethylaminoethyl)ether, N-methyl-N',N'-dimethylaminoethylpiperazine, N,N-dimethylcyclohexylamine, diazabicycloundecene, triethylenediamine, tetramethylethylenediamine, tetramethylhexamethylenediamine, trimethylaminoethylpiperazine, tripropylamine, and acid block products thereof. Among the amine resinification catalysts, imidazole compounds are preferred from the viewpoint of catalytic activity, etc.

[0023] The imidazole compound is a compound having an imidazole skeleton, and is preferably an imidazole derivative in which at least one of the 1- and 2-positions of the imidazole is substituted with an alkyl group having 8 or less carbon atoms or an alkenyl group having 8 or less carbon atoms. The imidazole compound is more preferably a compound in which at least one of the 1st and 2nd positions is substituted with an alkyl group, and further preferably a compound in which both the 1st and 2nd positions are substituted with alkyl groups (1,2-dialkylimidazole). The alkyl groups substituted at the 1st and 2nd positions may be the same or different. The number of carbon atoms in the alkyl group is preferably 1 to 6, and more preferably 1 to 4. Suitable specific examples of the imidazole compound include 1,2-dimethylimidazole, 1-ethyl-2-methylimidazole, 1-methyl-2-ethylimidazole, 1,2-diethylimidazole, and 1-isobutyl-2-methylimidazole. Among them, 1,2-dimethylimidazole and 1-isobutyl-2-methylimidazole are preferred from the viewpoint of improving the activity of the catalyst in the presence of hydrofluoroolefin and from the viewpoint of quickly progressing the reaction. In addition, 1,2-dimethylimidazole is more preferred from the viewpoint of further improving storage stability. The amine-based resinification catalyst may be used alone or in combination of two or more kinds.

[0024] The content of the resinification catalyst is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, and further preferably 1 to 12 parts by mass, based on 100 parts by mass of the polyol.

[0025] (trimerization catalyst) Examples of the trimerization catalyst include alkali metal carboxylates, tertiary ammonium salts, quaternary ammonium salts, nitrogen-containing aromatic compounds, etc. Among them, from the viewpoint of suppressing the increase in density of the polyurethane foam formed in a low-temperature environment, the trimerization catalyst preferably contains a quaternary ammonium salt, and more preferably contains a quaternary ammonium salt and an alkali metal carboxylate.

[0026] When used together with the later-described critical, subcritical or liquid carbon dioxide, the quaternary ammonium salt exhibits particularly good foaming properties and tends to suppress densification in a low-temperature environment. In addition, by using a quaternary ammonium salt and an alkali metal carboxylate in combination, the foaming properties are further improved due to two-stage foaming, and densification in low-temperature environments can be easily suppressed.

[0027] The weight ratio of the quaternary ammonium salt and the alkali metal carboxylate (quaternary ammonium salt / alkali metal carboxylate) is preferably 1 / 1 to 6 / 1, more preferably 1.2 / 1 to 5 / 1, and even more preferably 1.5 / 1 to 3 / 1. When the weight ratio is equal to or greater than these lower limits, the foaming property is improved, and densification in a low-temperature environment is easily suppressed. On the other hand, when the weight ratio is equal to or less than these upper limits, the workability by spraying is improved.

[0028] The content of the quaternary ammonium salt is preferably 0.1 to 20 parts by mass, more preferably 1 to 15 parts by mass, and further preferably 2 to 10 parts by mass, based on 100 parts by mass of the polyol. The content of the alkali metal carboxylate is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 1 to 5 parts by mass, based on 100 parts by mass of the polyol.

[0029] Examples of the alkali metal carboxylate include potassium 2-ethylhexanoate and potassium acetate. Examples of the quaternary ammonium salt include tetramethylammonium salt, tetraethylammonium salt, tetraphenylammonium salt, triethylmonomethylammonium salt, quaternary ammonium carboxylate, etc. A specific example of a suitable carboxylic acid in the quaternary ammonium carboxylate is at least one selected from the group consisting of 2-ethylhexanoic acid, 2,2-dimethylpropanoic acid, acetic acid, and formic acid. Examples of tertiary ammonium salts include trimethylammonium salts, triethylammonium salts, and triphenylammonium salts. Examples of the nitrogen-containing aromatic compounds include tris(dimethylaminomethyl)phenol, 2,4-bis(dimethylaminomethyl)phenol, and 2,4,6-tris(dialkylaminoalkyl)hexahydro-S-triazine.

[0030] The content of the trimerization catalyst is preferably 0.2 to 35 parts by mass, more preferably 1 to 30 parts by mass, and further preferably 3 to 15 parts by mass, based on 100 parts by mass of the polyol.

[0031] <Polyol> Examples of the polyol contained in the polyol composition include polylactone polyols, polycarbonate polyols, aromatic polyols, alicyclic polyols, polyester polyols, polymer polyols, and polyether polyols.

[0032] Examples of the polylactone polyol include polypropiolactone glycol, polycaprolactone glycol, and polyvalerolactone glycol. Examples of polycarbonate polyols include polyols obtained by dealcoholization reaction of hydroxyl group-containing compounds such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, and nonanediol with ethylene carbonate, propylene carbonate, and the like.

[0033] Examples of aromatic polyols include bisphenol A, bisphenol F, phenol novolac, and cresol novolac. Examples of alicyclic polyols include cyclohexanediol, methylcyclohexanediol, isophoronediol, dicyclohexylmethanediol, and dimethyldicyclohexylmethanediol.

[0034] Examples of polyester polyols include polymers obtained by dehydration condensation of polybasic acids and polyhydric alcohols, and condensates of hydroxycarboxylic acids and the above-mentioned polyhydric alcohols. Examples of polybasic acids include adipic acid, azeoic acid, sebacic acid, isophthalic acid (m-phthalic acid), terephthalic acid (p-phthalic acid), and succinic acid. Examples of polyhydric alcohols include bisphenol A, ethylene glycol, 1,2-propylene glycol, 1,4-butanediol, diethylene glycol, 1,6-hexane glycol, and neopentyl glycol. Examples of hydroxycarboxylic acids include castor oil and reaction products of castor oil and ethylene glycol.

[0035] Examples of the polymer polyol include polymers obtained by graft polymerizing an ethylenically unsaturated compound such as acrylonitrile, styrene, methyl acrylate, or methacrylate with an aromatic polyol, an alicyclic polyol, an aliphatic polyol, or a polyester polyol, or polybutadiene polyol, or hydrogenated products thereof.

[0036] Examples of polyether polyols include polymers obtained by ring-opening polymerization of at least one alkylene oxide, such as ethylene oxide, propylene oxide, and tetrahydrofuran, in the presence of at least one low-molecular-weight active hydrogen compound having two or more active hydrogens. Examples of low-molecular-weight active hydrogen compounds having two or more active hydrogens include diols, such as bisphenol A, ethylene glycol, propylene glycol, butylene glycol, and 1,6-hexanediol; triols, such as glycerin and trimethylolpropane; and amines, such as ethylenediamine and butylenediamine.

[0037] The polyol used in the present invention preferably contains at least one selected from polyester polyols and polyether polyols, and more preferably contains at least a polyester polyol. Among them, it is more preferable to contain a polyester polyol obtained by dehydration condensation of a polybasic acid having an aromatic ring, such as isophthalic acid (m-phthalic acid) or terephthalic acid (p-phthalic acid), and a dihydric alcohol, such as bisphenol A, ethylene glycol, or 1,2-propylene glycol. The content of the polyester polyol in 100 parts by mass of the polyol is preferably 50 parts by mass or more, more preferably 80 parts by mass or more, and even more preferably 90 parts by mass or more.

[0038] The hydroxyl value of the polyol is preferably 20 to 300 mgKOH / g, more preferably 30 to 275 mgKOH / g, and even more preferably 50 to 250 mgKOH / g. When the hydroxyl value of the polyol is equal to or less than the upper limit, the viscosity of the polyol liquid does not become excessively high, which is preferable from the viewpoint of handling, etc. On the other hand, when the hydroxyl value of the polyol is equal to or more than the lower limit, the crosslink density of the polyurethane foam increases, thereby increasing the strength. The hydroxyl value of the polyol can be measured in accordance with JIS K 1557-1:2007.

[0039] <Filler> The polyol composition contains a filler. By containing the filler, it is possible to impart a function according to the type of filler to the polyurethane foam. The filler preferably contains a flame retardant. By using the flame retardant as the filler, it is possible to impart high flame retardant performance to the polyurethane foam. The flame retardant used as the filler is preferably a solid flame retardant. By using a solid flame retardant, the flame retardancy can be more effectively improved. Note that a solid flame retardant is a flame retardant that is solid at room temperature (23°C) and normal pressure (1 atm). Examples of solid flame retardants include phosphorus-based flame retardants, boron-containing flame retardants, bromine-containing flame retardants, phosphate-containing flame retardants, chlorine-containing flame retardants, antimony-containing flame retardants, metal hydroxides, needle fillers, carbonate-based flame retardants, and carbon black.

[0040] (Red phosphorus flame retardant) The red phosphorus-based flame retardant may be made of red phosphorus alone, may be red phosphorus coated with a resin, a metal hydroxide, a metal oxide, or may be red phosphorus mixed with a resin, a metal hydroxide, a metal oxide, or the like. The resin that coats the red phosphorus or mixes with the red phosphorus is not particularly limited, but examples thereof include thermosetting resins such as phenol resin, epoxy resin, unsaturated polyester resin, melamine resin, urea resin, aniline resin, and silicone resin. From the viewpoint of flame retardancy, metal hydroxide is preferable as the compound to be coated or mixed. The metal hydroxide to be used may be appropriately selected from those described later.

[0041] (Boron-containing flame retardants) Examples of boron-containing flame retardants include borax, boron oxide, boric acid, borates, etc. Examples of boron oxide include diboron trioxide, boron trioxide, diboron dioxide, tetraboron trioxide, and tetraboron pentoxide. Examples of borates include borates of alkali metals, alkaline earth metals, elements of Groups 4, 12, and 13 of the periodic table, and ammonium. Specific examples include alkali metal borates such as lithium borate, sodium borate, potassium borate, and cesium borate, alkaline earth metal borates such as magnesium borate, calcium borate, and barium borate, zirconium borate, zinc borate, aluminum borate, and ammonium borate. The boron-containing flame retardants may be used alone or in combination of two or more kinds. Preferably, the boron-containing flame retardant is a borate, more preferably zinc borate.

[0042] (Bromine-containing flame retardants) The bromine-containing flame retardant is not particularly limited as long as it contains bromine in its molecular structure and is a solid at room temperature and pressure. Examples of the bromine-containing flame retardant include brominated aromatic ring-containing aromatic compounds. Examples of the brominated aromatic ring-containing aromatic compound include monomeric organic bromine compounds such as hexabromobenzene, pentabromotoluene, hexabromobiphenyl, decabromobiphenyl, decabromodiphenyl ether, octabromodiphenyl ether, hexabromodiphenyl ether, bis(pentabromophenoxy)ethane, ethylene bis(pentabromophenyl), ethylene bis(tetrabromophthalimide), and tetrabromobisphenol A.

[0043] In addition, the brominated aromatic ring-containing aromatic compound may be a bromine compound polymer.Specific examples include brominated polycarbonates such as polycarbonate oligomers produced from brominated bisphenol A as a raw material, copolymers of this polycarbonate oligomer and bisphenol A, and diepoxy compounds produced by the reaction of brominated bisphenol A and epichlorohydrin.Furthermore, examples include brominated epoxy compounds such as monoepoxy compounds obtained by the reaction of brominated phenols and epichlorohydrin, poly(brominated benzyl acrylate), brominated phenol condensates of brominated polyphenylene ether, brominated bisphenol A, and cyanuric chloride, brominated (polystyrene), poly(brominated styrene), brominated polystyrene such as crosslinked brominated polystyrene, crosslinked or non-crosslinked brominated poly(-methylstyrene), and the like. In addition, compounds other than brominated aromatic ring-containing aromatic compounds such as hexabromocyclododecane may be used. These bromine-containing flame retardants may be used alone or in combination of two or more. Among the above, brominated aromatic ring-containing aromatic compounds are preferred, and among them, monomeric organic bromine compounds such as ethylenebis(pentabromophenyl) are preferred.

[0044] (Phosphate-containing flame retardants) Examples of the phosphate-containing flame retardant include phosphates consisting of salts of various phosphoric acids and at least one metal or compound selected from metals in Groups IA to IVB of the periodic table, ammonia, aliphatic amines, aromatic amines, and heterocyclic compounds containing nitrogen in the ring. The phosphoric acid is not particularly limited, but examples thereof include monophosphoric acid, pyrophosphoric acid, and polyphosphoric acid. Examples of metals in Groups IA to IVB of the periodic table include lithium, sodium, calcium, barium, iron (II), iron (III), and aluminum. Examples of the aliphatic amine include methylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, piperazine, etc. Examples of the aromatic amine include aniline, o-triidine, 2,4,6-trimethylaniline, anisidine, 3-(trifluoromethyl)aniline, etc. Examples of the heterocyclic compound containing nitrogen in the ring include pyridine, triazine, melamine, etc.

[0045] Specific examples of phosphate-containing flame retardants include monophosphates such as aluminum triphosphate, pyrophosphates, polyphosphates, etc. Here, the polyphosphates are not particularly limited, but include, for example, ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium amide polyphosphate, aluminum polyphosphate, etc. The phosphate-containing flame retardant may be used alone or in combination of two or more of the above-mentioned compounds.

[0046] (Chlorine-containing flame retardants) Chlorine-containing flame retardants include those commonly used in flame-retardant resin compositions, such as polychlorinated naphthalenes, chlorendic acid, and dodecachlorododecahydrodimethanodibenzocyclooctene sold under the trade name "Dechlorane Plus."

[0047] (Antimony-containing flame retardants) Examples of antimony-containing flame retardants include antimony oxide, antimony salts, and pyroantimony salts. Examples of antimony oxide include antimony trioxide and antimony pentoxide. Examples of antimony salts include sodium antimonate and potassium antimonate. Examples of pyroantimonate include sodium pyroantimonate and potassium pyroantimonate. The antimony-containing flame retardants may be used alone or in combination of two or more. The preferred antimony-containing flame retardant for use in the present invention is antimony trioxide.

[0048] (metal hydroxide) Examples of metal hydroxides include magnesium hydroxide, calcium hydroxide, aluminum hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, titanium hydroxide, zinc hydroxide, copper hydroxide, vanadium hydroxide, tin hydroxide, etc. The metal hydroxides may be used alone or in combination of two or more kinds.

[0049] (Needle filler) Examples of needle-like fillers include potassium titanate whiskers, aluminum borate whiskers, magnesium-containing whiskers, silicon-containing whiskers, wollastonite, sepiolite, zonolite, elestadite, boehmite, rod-shaped hydroxyapatite, glass fibers, carbon fibers, graphite fibers, metal fibers, slag fibers, gypsum fibers, silica fibers, alumina fibers, silica alumina fibers, zirconia fibers, boron nitride fibers, boron fibers, and stainless steel fibers. These needle-like fillers can be used alone or in combination of two or more.

[0050] The aspect ratio (length / diameter) of the needle-like filler used in the present invention is preferably in the range of 5 to 50, and more preferably in the range of 10 to 40. The aspect ratio can be determined by observing the needle-like filler with a scanning electron microscope and measuring its length and width.

[0051] (carbonate flame retardant) Examples of carbonate-based flame retardants include calcium carbonate, magnesium carbonate, zinc carbonate, and barium carbonate, and among these, calcium carbonate is preferred.

[0052] The amount of the solid flame retardant is not particularly limited, but is, for example, 10 to 200 parts by mass, preferably 20 to 150 parts by mass, and more preferably 40 to 120 parts by mass, relative to 100 parts by mass of the polyol. By making the amount of the solid flame retardant equal to or greater than these lower limits, it is possible to impart appropriate flame retardancy to the polyurethane foam. By making the amount of the solid flame retardant equal to or less than these upper limits, it is possible to easily obtain a polyurethane foam with a small density difference depending on the location.

[0053] As the filler, inorganic fillers other than the above-mentioned flame retardants may be blended. As the inorganic filler, alumina, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, ferrites, dawsonite, hydrotalcite, calcium sulfate, barium sulfate, calcium silicate, talc, mica, montmorillonite, bentonite, activated clay, imogolite, sericite, glass beads, aluminum nitride, boron nitride, silicon nitride, various metal powders, magnesium sulfate, lead zirconate titanate, molybdenum sulfide, silicon carbide, various magnetic powders, fly ash, etc. may be appropriately used. The inorganic filler may be used alone or in combination of two or more.

[0054] The content of the filler in the polyol composition is, for example, 10 to 300 parts by mass, preferably 20 to 150 parts by mass, and more preferably 40 to 120 parts by mass, relative to 100 parts by mass of the polyol. By making the amount of the filler blended equal to or greater than these lower limits, it becomes easier to impart a function to the polyurethane foam according to the type of filler. By making the amount of the filler blended equal to or less than these upper limits, it becomes easier to obtain a polyurethane foam with less density difference depending on the location.

[0055] (Liquid flame retardant) The polyol composition may contain a liquid flame retardant. The liquid flame retardant is a flame retardant that is liquid at room temperature (23°C) and normal pressure (1 atm). A specific example of the liquid flame retardant is a phosphoric acid ester. Unlike a solid flame retardant, the liquid flame retardant is less likely to cause precipitation during storage and is easy to handle.

[0056] As the phosphoric acid ester, it is preferable to use a monophosphoric acid ester, a condensed phosphoric acid ester, etc. Examples of the monophosphoric acid ester include trialkyl phosphates such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, and tri(2-ethylhexyl)phosphate, halogen-containing phosphoric acid esters such as tris(β-chloropropyl)phosphate, trialkoxy phosphates such as tributoxyethyl phosphate, aromatic ring-containing phosphoric acid esters such as tricresyl phosphate, trixylenyl phosphate, tris(isopropylphenyl)phosphate, cresyl diphenyl phosphate, and diphenyl(2-ethylhexyl)phosphate, and acidic phosphoric acid esters such as monoisodecyl phosphate and diisodecyl phosphate.

[0057] Examples of the condensed phosphate ester include aromatic condensed phosphate esters such as trialkyl polyphosphate, resorcinol polyphenyl phosphate, bisphenol A polycresyl phosphate, and bisphenol A polyphenyl phosphate. Commercially available condensed phosphate esters include, for example, "CR-733S", "CR-741", and "CR747" manufactured by Daihachi Chemical Industry Co., Ltd., and "ADEKA STAB PFR" and "FP-600" manufactured by ADEKA Corporation.

[0058] The liquid flame retardant may be one of the above-mentioned compounds, or two or more of them may be used in combination. Among them, from the viewpoint of facilitating the production of polyurethane foam and improving the flame retardancy of the polyurethane foam, monophosphate ester is preferred, and tris(β-chloropropyl)phosphate is more preferred.

[0059] When a liquid flame retardant is contained, the blending amount thereof is preferably from 5 to 80 parts by mass, more preferably from 10 to 70 parts by mass, and further preferably from 20 to 60 parts by mass, based on 100 parts by mass of the polyol.

[0060] (Foam stabilizer) The polyol composition may contain a foam stabilizer, which improves the foamability of the urethane resin composition obtained by mixing the polyol composition and the polyisocyanate composition. Examples of the foam stabilizer include surfactants such as polyoxyalkylene-based foam stabilizers such as polyoxyalkylene alkyl ethers, and silicone-based foam stabilizers such as organopolysiloxanes. These foam stabilizers may be used alone or in combination of two or more. When a foam stabilizer is used, the blending amount is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and even more preferably 1 to 5 parts by mass, relative to 100 parts by mass of polyol. When the blending amount of the foam stabilizer is equal to or more than these lower limits, the urethane resin composition is easily foamed, and a homogeneous polyurethane foam is easily obtained. When the blending amount of the foam stabilizer is equal to or less than these upper limits, the balance between the production cost and the obtained effect is good.

[0061] (Other ingredients) The polyol composition may contain, as necessary, one or more selected from additives such as phenol-based, amine-based, and sulfur-based antioxidants, heat stabilizers, metal inhibitors, antistatic agents, stabilizers, crosslinking agents, lubricants, softeners, pigments, and tackifying resins, tackifiers such as polybutene and petroleum resins, etc., within the scope of the present invention.

[0062] [Urethane resin composition] The urethane resin composition of the present invention contains a polyol composition and a polyisocyanate composition containing a polyisocyanate. More specifically, the urethane resin composition is prepared by mixing the polyol composition and the polyisocyanate composition, and then the polyol and the polyisocyanate react with each other to foam and harden to form a polyurethane foam.

[0063] (Polyisocyanate composition) The polyisocyanate composition of the present invention contains a polyisocyanate. As the polyisocyanate, a known polyisocyanate used for forming a polyurethane foam can be used, and examples thereof include aromatic polyisocyanates, alicyclic polyisocyanates, and aliphatic polyisocyanates. Examples of aromatic polyisocyanates include phenylene diisocyanate, tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, and polymethylene polyphenyl polyisocyanate.

[0064] Examples of the alicyclic polyisocyanate include cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and dimethyldicyclohexylmethane diisocyanate.

[0065] Examples of the aliphatic polyisocyanate include methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate.

[0066] Among these, from the viewpoints of ease of use and availability, aromatic polyisocyanates are preferred, and diphenylmethane diisocyanate is more preferred. The polyisocyanates may be used alone or in combination of two or more.

[0067] The polyisocyanate composition may contain the above-mentioned foaming agent, filler, etc., but preferably consists of polyisocyanate alone.

[0068] (Isocyanate Index) The isocyanate index of the urethane resin composition of the present invention is not particularly limited, but is preferably 120 to 500, more preferably 150 to 400. If the isocyanate index is equal to or greater than the lower limit, the amount of polyisocyanate relative to the polyol becomes excessive, which makes it easier for isocyanurate bonds to be formed by the trimer of polyisocyanate, thereby improving the flame retardancy of the polyurethane foam. If the isocyanate index is equal to or less than the upper limit, the balance between the flame retardancy and the production cost of the resulting polyurethane foam is good.

[0069] The isocyanate index can be calculated by the following method. Isocyanate Index = equivalents of polyisocyanate ÷ (equivalents of polyol + equivalents of water) × 100 Here, each equivalent number can be calculated as follows: Equivalent number of polyisocyanate = Amount of polyisocyanate used (g) × NCO content (mass%) / Molecular weight of NCO (mol) × 100 Equivalent weight of polyol = OHV × amount of polyol used (g) ÷ molecular weight of KOH (mmol) OHV is the hydroxyl value of the polyol (mg KOH / g). Equivalents of water = amount of water used (g) / molecular weight of water (mol) × number of OH groups in water In the above formulas, the molecular weight of NCO is 42 (mol), the molecular weight of KOH is 56100 (mmol), the molecular weight of water is 18 (mol), and the number of OH groups in water is 2.

[0070] (carbon dioxide) The urethane resin composition of the present invention preferably contains critical, subcritical or liquid carbon dioxide. By using the above-mentioned predetermined amounts of the blowing agent and the carbon dioxide in combination, foaming is effectively promoted and the increase in density of the polyurethane foam in a low-temperature environment can be suppressed. Supercritical, subcritical or liquid carbon dioxide is carbon dioxide gas that has been pressurized at a predetermined temperature to a supercritical state, subcritical state or liquid state. Specifically, supercritical carbon dioxide is carbon dioxide in a fluid state where both the pressure and temperature exceed the critical points, i.e., the critical pressure and the critical temperature. Subcritical carbon dioxide is carbon dioxide in a liquid state where the pressure is equal to or higher than the critical pressure and the temperature is lower than the critical temperature, or carbon dioxide in a liquid state where the pressure is lower than the critical pressure and the temperature is higher than the critical temperature, or carbon dioxide in a state where the temperature and pressure are lower than the critical points but close to them. Liquid carbon dioxide is carbon dioxide that has been liquefied under temperature and pressure conditions higher than the triple point.

[0071] The content of supercritical, subcritical or liquid carbon dioxide in the urethane resin composition is preferably 0.1 to 4 parts by mass, more preferably 0.2 to 3 parts by mass, and even more preferably 0.3 to 2 parts by mass, per 100 parts by mass of polyol, from the viewpoint of suppressing densification of the polyurethane foam at low temperatures.

[0072] In addition, although details will be described later, supercritical, subcritical or liquid carbon dioxide is added to at least one of the polyol composition and the polyisocyanate composition during the production of polyurethane foam. After or simultaneously with the addition of the carbon dioxide, the polyol composition and the polyisocyanate composition are mixed, and the reaction between the polyol and the polyisocyanate proceeds to foam and harden, thereby forming a polyurethane foam. Carbon dioxide may be added alone or as a mixture of carbon dioxide and a blowing agent, preferably a mixture of carbon dioxide and a hydrofluoroolefin.

[0073] (density) A polyurethane foam is formed by foaming and curing the urethane resin composition. The core density of the polyurethane foam thus formed is preferably 25 to 45 kg / m from the viewpoints of low density and good dimensional stability. 3and more preferably 33 to 40 kg / m 3 and more preferably 33 to 36 kg / m 3 It is. The urethane resin composition of the present invention is preferably a urethane resin composition that results in a polyurethane foam having a core density in the above-mentioned range. The density of the polyurethane foam can be measured in accordance with JIS K7222. In this specification, the core density of a polyurethane foam means the density of the polyurethane foam excluding the skin layer, specifically, the density of the internal polyurethane foam excluding the surface layer of 5 mm from the formed polyurethane foam.

[0074] [Manufacturing method of polyurethane foam] The method for producing a polyurethane foam in the present invention is a method for producing a polyurethane foam by foaming and curing the above-mentioned urethane resin composition. The method preferably includes a step of adding critical, subcritical or liquid carbon dioxide to at least one of the polyol composition and the polyisocyanate composition. The amount of carbon dioxide added is preferably 0.1 to 4 parts by mass per 100 parts by mass of the polyol, and the reaction proceeds after the addition of the carbon dioxide.

[0075] (Step of adding carbon dioxide) The critical, subcritical or liquid carbon dioxide is preferably added to at least one of the polyol composition and the polyisocyanate composition before or simultaneously with mixing of the polyol composition and the polyisocyanate composition, and is preferably added to the polyol composition in consideration of ease of foam formation, etc. When carbon dioxide is added simultaneously with mixing of the polyol composition and the polyisocyanate composition, it is preferable to supply the critical, subcritical or liquid carbon dioxide to the position where both compositions are mixed.

[0076] More specifically, in the production method of the present invention, it is preferable to produce a polyurethane foam at a production site where the polyurethane foam is produced by providing a flow path for supplying critical, subcritical or liquid carbon dioxide, separate from a flow path for supplying a polyol composition and a flow path for supplying a polyisocyanate. In this way, by producing a polyurethane foam at the production site by adding critical, subcritical or liquid carbon dioxide in a system separate from both compositions, the polyol composition and the polyisocyanate composition can be well mixed, and the density and other properties can be easily uniformed, resulting in the formation of a polyurethane foam with excellent physical properties.

[0077] When adding supercritical, subcritical or liquid carbon dioxide, the carbon dioxide may be added alone or as a mixture of the carbon dioxide and a blowing agent, preferably as a mixture of the carbon dioxide and a hydrofluoroolefin. The mass ratio of the carbon dioxide to the blowing agent in the mixture (carbon dioxide / hydrofluoroolefin) is, for example, 0.05 to 5, preferably 0.1 to 2, and more preferably 0.2 to 1, from the viewpoint of improving the mixability of the composition.

[0078] The amount of supercritical, subcritical or liquid carbon dioxide added is preferably 0.1 to 4 parts by mass, more preferably 0.2 to 3 parts by mass, and further preferably 0.3 to 2 parts by mass, based on 100 parts by mass of polyol. When the amount of carbon dioxide added is within the above range, densification of the polyurethane foam at low temperatures can be easily suppressed.

[0079] A urethane resin composition is prepared by mixing the polyol composition and the polyisocyanate composition after or simultaneously with the addition of supercritical, subcritical or liquid carbon dioxide to at least one of the polyol composition and the polyisocyanate composition, and then the polyol and the polyisocyanate react with each other, and are foamed and cured to form a polyurethane foam.

[0080] In the present invention, when the polyol composition and the polyisocyanate composition are mixed and foamed and cured, various known methods for producing polyurethane foams can be used. For example, various methods can be applied, such as coating, injection, spraying, etc. Specifically, there are a method of coating an adherend with a urethane resin composition obtained by mixing a polyol composition and a polyisocyanate composition, followed by foaming and curing, a method of injecting a urethane resin composition into a structure having a hollow portion, followed by foaming and curing, and a method of spraying a urethane resin composition onto an adherend. In the present invention, since the polyurethane foam to be formed can be prevented from becoming densified in a low-temperature environment, a desired polyurethane foam can be formed by spraying even if the adherend is at a low temperature. The spraying is preferably performed using a spraying device equipped with a carbon dioxide supplying device. Specifically, the polyol composition and the polyisocyanate composition in separate containers are temperature-adjusted in the spraying device, and critical, subcritical or liquid carbon dioxide is supplied to either of the compositions by the carbon dioxide supplying device, and then the two compositions are mixed by collision at the tip of a spray gun, and the mixed liquid is misted by air pressure. EXAMPLES

[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. The components used in the examples and comparative examples are shown below.

[0082] <Polyol> (A-1) Polyester polyol (manufactured by Kawasaki Chemical Industries, Ltd., product name: Maximol RFK-505, hydroxyl value = 250 mg KOH / g)

[0083] <Liquid flame retardant> (B-1) Phosphate ester: Tris(β-chloropropyl)phosphate (manufactured by Daihachi Chemical Industry Co., Ltd., product name: TMCPP)

[0084] <Filler> (C-1) Ammonium polyphosphate (Clariant Chemicals, product name: Exolit AP422) (C-2) Melamine polyphosphate (Nissan Chemical Industries, product name: PHOSMEL-200) (C-3) Silicon-based needle-shaped filler (Kinseimatic Co., Ltd., product name: SH1250) (C-4) Zinc borate (manufactured by Hayakawa Shoji Co., Ltd., product name: FirebrakeZB) (C-5) Calcium carbonate (Bihoku Powder Industry Co., Ltd., product name: BF300) (C-6) Carbon black (manufactured by Tokai Carbon Co., Ltd., product name: THERMAX) (C-7) Ethylenebis(pentabromophenyl) (manufactured by Albemarle, product name: SAYTEX8010) (C-8) Red phosphorus (manufactured by Rinkagaku Kogyo Co., Ltd., product name: Nova Excel 140)

[0085] <Foaming agent> (D-1) trans-1-chloro-3,3,3-trifluoropropene (HFO-1233zd(E)) (Honeywell, product name: Solstice LBA) (D-2) (Z)-1,1,1,4,4,4-Hexafluorobutan-2-ene (HFO-1336mzz(Z)) (manufactured by Chemours, product name: Opteon1100) (D-3) (Z)-1-chloro-2,3,3,3,-tetrafluoropropene (HFO-1224yd(Z)) (manufactured by Asahi Glass Co., Ltd., product name: AMOLEA 1224yd) (D-4) Ion-exchanged water

[0086] <Carbon dioxide> (D-5) Liquid carbon dioxide (D-6) Mixture of liquid carbon dioxide and HFO-1234ze, manufactured by Tokyo Koatsu Yamazaki Co., Ltd., liquid CO2:HFO-1234ze=3:7 (weight ratio)

[0087] <Trimerization catalyst> (E-1) Quaternary ammonium salt 2-ethylhexanoic acid hydroxybutyltrimethylammonium salt (Kao Corporation, product name: Kaolizer No. 420) concentration: approximately 100% by mass (E-2) Alkaline metal carboxylate Potassium 2-ethylhexanoate (manufactured by Evonik, product name: DABCO K-15) concentration: approx. 74%

[0088] <Resinification catalyst> (F-1) Amine-based resinification catalyst 1,2-dimethylimidazole (Kao Corporation, product name: Kaolizer No. 390) concentration 65-75% by mass (F-2) Bismuth-based catalyst: Bismuth 2-ethylhexanoate (manufactured by Nitto Kasei Co., Ltd., product name: Bi28), concentration 81 to 90% by mass (F-3) Tin-based catalyst Dioctyltin dineodecanoate (manufactured by Nitto Kasei Co., Ltd., product name: Neostan U-830) concentration: approximately 99% by mass

[0089] [Examples 1 to 5, 14 to 20, Comparative Examples 1 to 2] (Foam Density Rating) The polyol composition was prepared by mixing the types of polyol, liquid flame retardant, filler, blowing agent, trimerization catalyst, and resinification catalyst shown in Tables 1 to 3 in the amounts shown in the tables. A polyisocyanate composition made of diphenylmethane diisocyanate (MDI) was prepared separately. These compositions were introduced into a spray machine (Graco Spray Machine H-25) and mixed to form a urethane resin composition, which was sprayed onto a flexible board to form a polyurethane foam. The mixing ratio of the polyol composition and the polyisocyanate composition was 1:1 by volume, and the temperature of the flexible board was (0°C). The spraying was carried out in two separate steps (spraying again on a foam that had already been formed, forming a foam in layers). The surface skin layer was removed from the formed polyurethane foam to reveal the core layer, and a 100 mm x 100 mm x 25 mm piece of polyurethane foam was cut out. The core density was calculated from its mass and evaluated according to the following criteria. 〇: 45kg / m 3 less than ×:45kg / m 3 End

[0090] (Dimensional stability of foam) A test piece having a size of 100 mm x 100 mm x 25 mm, including the inner skin layer (the skin layer formed by the first spraying), was cut out from the polyurethane foam obtained by spraying as described above. The cut test piece was left to stand in an environment of -30°C for 48 hours, and then the test piece was placed on a horizontal table and visually observed for the presence or absence of warping, and evaluated according to the following criteria. 〇: No warping is observed ×: Warping was observed

[0091] (foaming speed) A polyol composition and a polyisocyanate composition were prepared in the same manner as in the above-mentioned "foam density evaluation". Then, a urethane resin composition in which the polyol composition and the polyisocyanate composition were mixed at a volume ratio of 1:1 was discharged onto a flexible board at 0°C, and the time T from when foaming started to when it became cloudy was measured. Evaluation was made according to the following criteria based on the time T. A score of "3" or higher was considered to be acceptable according to the following criteria. 5: Time T is less than 4 seconds 4: Time T is 4 seconds or more and less than 8 seconds 3: Time T is between 8 and 12 seconds 2: Time T is between 12 and 16 seconds 1: Time T is 16 seconds or more

[0092] [Examples 6 to 13, Comparative Example 3] (Foam Density Rating) The polyol composition was prepared by mixing the types of polyol, liquid flame retardant, filler, blowing agent, trimerization catalyst, and resinification catalyst shown in Tables 1 to 3 in the amounts shown in the tables. The polyol composition was introduced into an on-site foaming spraying device (manufactured by Asahi Organic Chemicals Co., Ltd., product name: AYK-1000 series) equipped with a liquefied carbon dioxide supply device, and carbon dioxide of the type and amount shown in each table was supplied to the polyol composition in the flow path of the polyol composition and mixed. The polyol composition mixed with the carbon dioxide and a polyisocyanate composition consisting of polyisocyanate (MDI) were contact-mixed to form a urethane resin composition. This was sprayed onto a flexible board to form a polyurethane foam. The mixing ratio of the polyol composition and the polyisocyanate composition was 1:1 by volume, and the temperature of the flexible board was (0°C). The spraying was carried out twice (spraying again on a foam once formed to form a foam in layers). The measurement and evaluation criteria for foam density were the same as in Example 1.

[0093] (Dimensional stability of foam) The polyurethane foams produced in the "foam density evaluation" of Examples 6 to 13 and Comparative Example 3 were used to evaluate the dimensional stability of the foams using the same method and criteria as in Example 1.

[0094] (foaming speed) In Examples 6 to 13 and Comparative Example 3, the urethane resin composition in the "foam density evaluation" was discharged onto a flexible board at 0°C, and the time T from when foaming started to when the composition became cloudy was measured. The evaluation criteria for the foaming speed were the same as in Example 1.

[0095] (Overall Judgment) In each of the Examples and Comparative Examples, an overall evaluation was made according to the following criteria. ○: Both foam density and dimensional stability are rated as ○ ×: At least one of the foam density and dimensional stability is evaluated as ×.

[0096] [Table 1]

[0097] [Table 2]

[0098] [Table 3]

[0099] From the results of each example, it was found that the polyol composition of the present invention and a urethane resin composition containing the polyol composition can suppress densification in a low-temperature environment and form a polyurethane foam having excellent dimensional stability. On the other hand, it was found that the polyurethane foams formed from the polyol compositions of the respective Comparative Examples had high density or poor dimensional stability.

Claims

1. a polyol composition comprising a polyol, a filler, a foaming agent, a resinification catalyst and a trimerization catalyst, the content of the foaming agent being 35 to 60 parts by mass per 100 parts by mass of the polyol; a polyisocyanate composition comprising a polyisocyanate; and carbon dioxide in a critical, subcritical or liquid state; The blowing agent is at least one selected from the group consisting of water and hydrofluoroolefins, the resinification catalyst comprises a metal-based resinification catalyst and an amine-based resinification catalyst, the metal-based resinification catalyst comprises at least one selected from the group consisting of a bismuth-based catalyst and a tin-based catalyst, and the amine-based resinification catalyst comprises an imidazole compound; The urethane resin composition, wherein the trimerization catalyst comprises a quaternary ammonium salt.

2. The core density of the resulting polyurethane foam is 25 to 45 kg / m 3 The urethane resin composition according to claim 1 ,

3. 3. The urethane resin composition according to claim 1, wherein the content of the metal-based resinification catalyst is 0.1 to 12 parts by mass per 100 parts by mass of the polyol.

4. The urethane resin composition according to any one of claims 1 to 3, wherein the trimerization catalyst contains a quaternary ammonium salt and an alkali metal carboxylate, and the weight ratio thereof (quaternary ammonium salt / alkali metal carboxylate) is 1 / 1 to 6 / 1.

5. The urethane resin composition according to any one of claims 1 to 4, wherein the content of the trimerization catalyst is 1 to 30 parts by mass per 100 parts by mass of the polyol.

6. A method for producing a polyurethane foam by foaming and curing the urethane resin composition according to any one of claims 1 to 5, comprising the steps of: The method includes a step of adding critical, subcritical or liquid carbon dioxide to at least one of a polyol composition and a polyisocyanate composition, the amount of carbon dioxide added being 0.1 to 4 parts by mass per 100 parts by mass of the polyol, A method for producing a polyurethane foam, wherein the reaction proceeds after the addition of carbon dioxide.

Citation Information

Patent Citations

  • Polyurethane foam production method and polyurethane foam produced thereby

    JP2016188329A

  • Polyol composition and polyurethane foam

    JP2018178096A

  • Method for producing polyurethane foam

    JP2020070409A

  • Method for producing polyurethane foam

    JP2020070410A

  • Method for producing polyurethane foam

    JP2020070411A